PATIENT SAFETY IN GENERAL ANESTHESIA: IMPACT OF OPIOID USE AND PHARMACEUTICAL MANAGEMENT STRATEGIES (REMUNOM, 2025)
General anesthesia is fundamental in medium- and high-complexity surgical procedures, with opioids widely used for their potent analgesic action and ability to control the surgical stress response. However, these drugs can cause significant adverse effects, such as nausea, sedation, respiratory depression, and dependence, requiring safe management and monitoring strategies. In this scenario, the clinical pharmacist plays an essential role in implementing protocols, guiding the multidisciplinary team, and acting in the prevention of adverse events related to opioid use. This study aimed to characterize the main risks associated with the use of opioids in general anesthesia and to identify pharmaceutical strategies that contribute to patient safety. The research was developed through an integrative literature review, with searches conducted in the LILACS, PubMed, and SciELO databases, using DeCS descriptors combined with Boolean operators, in the groupings: "General Anesthesia" AND "Opioids" AND "Patient Safety" AND "Pharmaceutical Strategies". Articles published between 2015 and 2025, in Portuguese or English and with free access, were included, excluding duplicate studies or those unrelated to the topic. The results showed that interventions such as multimodal analgesia, continuous monitoring of respiratory function, and judicious use of antagonists, such as naloxone, significantly reduce perioperative complications. Furthermore, it was evident that the active presence of a pharmacist in the perioperative period strengthens pharmacovigilance, improves medication safety, and contributes to the standardization of good anesthetic practices. Thus, the study reinforces the need to integrate pharmaceutical strategies into anesthetic protocols, promoting safer, more efficient, and individualized care.